Exploring the Impact of Pre-course High-Fidelity Simulation on Professional Socialization of Medical Students in Emergency Medicine Internship Rotation—A Qualitative Approach - Chang, Yu-Che; Nkambule, Nothando Sithulile; Chen, Shou-Yen; Hsieh, Ming-Ju; Chaou, Chung-Hsien (Frontiers in Medicine, 2022)
Background: This study sought to address the issue of interns’ limited opportunities for participation in real clinical practice through the integration of simulation-based education into an internship rotation. The aims were to explore interns’ conceptualization of their learning opportunities and experiences in the workplace during an emergency medicine (EM) block internship. In addition, the study explored how participating in the pre-rotation high-fidelity simulation (HFS) orientation influenced interns’ perception of their transition, participation and learning experiences in the real EM setting. Methods: We implemented a newly developed pre-EM rotation orientation curriculum for interns. This orientation took place on the first day of the two-week EM internship rotation. Two focus group discussions were held after each simulation training, one immediately after simulation to understand the students’ perception and the educational impact of this activity, the other at the end of EM rotation to explore and compare their roles and perception in both simulation activity and the real clinical practice. A total of 151 seventh-year medical students enrolled in the pre-course HFS and post-hoc focus group discussions between 2017 and 2019. We applied thematic analysis to systemically identify, examine, and construct themes. Results: Four major themes were constructed from the data; 1. Challenges in finding authentic learning experiences within the context of emergency medicine; 2. Effectiveness of the pre-course HFS 3. Limitations of EM internship rotation curriculum and pre-course simulation. 4. Suggestions for EM block-internship curriculum reforms. Our study’s key findings indicate that pre-rotation orientation HFS activity, which offered a psychologically safe space for students to explore facets of EM and gain a contextualized understanding of the emergency work culture and environment, was essential for enhancing students’ ability to identify and maximize practice affordances in real workplace. Conclusion: Simulation, facilitates interns’ negotiation of legitimate peripheral participation opportunities as they transition into the EM community of practice during their block internship rotation; putting students at the center of the learning process.